Britain after three years at war, 1943 (1943)
1943 1939-1945 "Britain after three years at war, 1943" [HFR0180], 1943 This pictorial poster chart, published by the Ministry of Information in March 1943, provided statistics on labour supply, national expenditure, industrial production, rationing and war damage.